2009
DOI: 10.9775/kvfd.2009.518
|View full text |Cite
|
Sign up to set email alerts
|

Tuj ve Morkaraman Koyunlarının Kafatasında Karşılaştırmalı Morfometrik Bir Çalışma

Abstract: SummaryThis study was undertaken to reveal morphometric skull features of the Tuj and Morkaraman sheep. The skulls of 10 months old 6 male Tuj and 6 male Morkaraman sheep were used. A number of 38 craniometric measurements were taken from skulls of both species. Craniofacial indices were also calculated. There were no significant differences determined between the heads of these species except the measurement which displayed the width between the two orbita (entorbitale entorbitale = least breadth between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…In the study, profile length of Hamdani cranium was calculated as 216.71 ± 3.42 mm and 228.51 ± 7.89 mm in females and males, respectively. These lengths were found as 248.17 ± 9.73 mm (Jashari et al, 2022) and 245.80 ± 19.62 mm in Sharri ewe and ram, 245.25 ± 10.24 mm and 257.98 ± 15.81 mm in Bardhoka ewe and ram (Gündemir et al, 2020), 204.49 ± 9.71 mm and 198.09 ± 7.69 mm in tuj and morkaraman sheep (Ozcan et al, 2010), respectively, 186.7 ± 0.66 mm in markhoz goat (Goodarzi & Shah Hoseini, 2014), and 247.2 ± 0.93 mm in kagani goat (Sarma, 2006). Such differences between animal species and breeds are thought to be due to the geographical environment in which they were raised, their care and feeding conditions, and breed specificity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study, profile length of Hamdani cranium was calculated as 216.71 ± 3.42 mm and 228.51 ± 7.89 mm in females and males, respectively. These lengths were found as 248.17 ± 9.73 mm (Jashari et al, 2022) and 245.80 ± 19.62 mm in Sharri ewe and ram, 245.25 ± 10.24 mm and 257.98 ± 15.81 mm in Bardhoka ewe and ram (Gündemir et al, 2020), 204.49 ± 9.71 mm and 198.09 ± 7.69 mm in tuj and morkaraman sheep (Ozcan et al, 2010), respectively, 186.7 ± 0.66 mm in markhoz goat (Goodarzi & Shah Hoseini, 2014), and 247.2 ± 0.93 mm in kagani goat (Sarma, 2006). Such differences between animal species and breeds are thought to be due to the geographical environment in which they were raised, their care and feeding conditions, and breed specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The largest area of cranium is the frontal region in ruminants (Greatest frontal breadth) (Ozcan et al, 2010; Yılmaz & Demircioglu, 2020). The studies reported this distance as 101.66 ± 1.69 mm in tuj sheep, 102.98 ± 2.52 mm (Ozcan et al, 2010) in morkaraman sheep, 115.07 ± 7.74 mm on average in Awassi sheep (Yılmaz & Demircioglu, 2020), 89.1 ± 0.18 mm in Markhoz goat (Goodarzi & Shah Hoseini, 2014), and 104.4 ± 0.29 mm in Mehraban sheep (Karimi et al, 2011). In the study, the largest area of Hamdani cranium was found as 216.71 ± 3.42 mm in ewe and 228.51 ± 7.89 mm in ram.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations